Kepastian Hukum Perjanjian Perkawinan Secara Otentik Yang Tidak Di daftarkan Oleh Notaris - Addinur Addinur; Gunawan Djajaputra (Dinasti Research, 2025)
This research examines the legal certainty of marriage agreements depending on the form and process of making them. Based on Article 15 paragraph (1) of the Notary Law, an authentic deed made before a notary has higher legal force than a private deed. An authentic agreement remains binding on the parties in accordance with Article 1320 of the Civil Code, but without registration at the marriage registration office, the agreement only applies privately and does not bind third parties. The provisions in Article 29 paragraph (1) of the Marriage Law and Article 22 of PMA Number 20 of 2019 emphasize the importance of registration agreements for formal validity which protects against third party claims. However, the problems that arose due to the Constitutional Court's lack of clarity regarding the obligation to authenticate documents created permission for implementation. Minister of Home Affairs Regulation Number 108 of 2019 and PMA Number 20 of 2019 require that marriage agreements be authentic, but this discrepancy often hampers the legal validity of private parties. Authentic deeds provide stronger protection by ensuring the parties' consent and reducing legal preservation risks. Therefore, the presence of a notary in making and registering marriage agreements is important to ensure legal certainty and protect the rights of couples.